Proyeksi Ketercapaian Bonus Demografi di Indonesia Tahun 2035 - Ani Nuryani; Aan Julia (Bandung Conference Series: Economics Studies, 2022)
Abstract. This paper presents a discussion of the projected achievement of the demographic bonus in Indonesia in 2035. The demographic bonus is a potential for economic growth which is marked by a high number of productive age population. Indonesia is predicted to experience a demographic bonus period in 2030-2040. This study aims to determine the effect of saving, school participation rate, labor force participation rate and dependency ratio on the level of per capita income. As well as discussing how the projected results of the demographic bonus achievement in Indonesia are seen through the level of income per capita in Indonesia in 2035. The data used in this study is secondary data originating from various sources in 1991-2020. The data analysis technique in this study uses time series data analysis with multiple linear regression models and the Forecasting method to project the achievement of the demographic bonus through Indonesia's per capita income in 2035. The results show that the variables of savings, school enrollment rates, labor force participation rates and dependency ratios are together have a significant effect on per capita income. Meanwhile, the projected results of the demographic bonus achievement based on the level of per capita income are thought to have not been achieved in 2035. Abstrak. Tulisan ini menampilkan pembahasan mengenai proyeksi ketercapaian bonus demografi di Indonesia tahun 2035. Bonus demografi merupakan potensi pertumbuhan ekonomi yang ditandai dengan tingginya jumlah penduduk usia produktif. Indonesia diprediksi akan mengalami periode bonus demografi pada tahun 2030-2040. Penelitian ini bertujuan untuk mengetahui pengaruh tabungan, angka partisipasi sekolah, tingkat partisipasi angkatan kerja dan dependency ratio terhadap tingkat pendapatan perkapita. Serta membahas bagaimana hasil proyeksi pencapaian bonus demografi di Indonesia yang dilihat melalui tingkat pendapatan perkapita di Indonesia tahun 2035. Data yang digunakan dalam penelitian ini adalah data sekunder yang berasal dari berbagai sumber tahun 1991-2020. Teknik analisis data dalam penelitian ini menggunakan analisis data time series dengan model regresi linear berganda dan metode Forecasting untuk memproyeksikan pencapaian bonus demografi melalui pendapatan perkapita Indonesia tahun 2035. Hasil penelitian menunjukkan bahwa variabel tabungan, angka partisipasi sekolah, tingkat partisipasi angkatan kerja dan dependency ratio secara bersama-sama berpengaruh secara signifikan terhadap pendapatan perkapita. Sedangkan hasil proyeksi pencapaian bonus demografi berdasarkan tingkat pendapatan perkapita diduga belum tercapai pada tahun 2035.